Disentangling the Influence of Recommender Attributes and News-Story Attributes: A Conjoint Experiment on Exposure and Sharing Decisions on Social Networking Sites. Issue 8 (14th September 2021) - Johannesson, Mikael Poul; Knudsen, Erik
Abstract: While news outlets still play an important role as a source of news, people increasingly receive their political information and news from social networking sites (SNSs). This study extends the literature on exposure and sharing decisions on SNSs by exploring how different attributes shape such decisions, how the two decision types differ, and by disentangling the role played by personal news recommendations and shared news stories on SNSs. As SNSs add a social dimension, exposure and sharing decisions are contingent not only upon the news story itself (news-story attributes) but also upon characteristics of the person who shares the story (recommender attributes). We designed a conjoint experiment to disentangle the effects of recommender and news-story attributes on the decision to recommend and read news and fielded it in a probability-based Norwegian online survey. The results suggest that committing to reading and sharing information are two similar yet distinct phenomena and that selective sharing is a stronger commitment than selective exposure. We also found evidence to suggest that selective sharing of news featuring a favored political party was contingent upon whether one also received information about the recommender attributes.